Monte Carlo characterization of PETALO, a full-body liquid xenon-based PET detector. (1st May 2022) - Renner, J.; Romo-Luque, C.; Aliaga, R.J.; Álvarez, V.; Ballester, F.; Benlloch-Rodríguez, J.M.; Carrión, J.V.; Cubero, D.; Díaz, J.; Esteve, R.; Gadea, R.; Generowicz, J.; et al.
Abstract: New detector approaches in Positron Emission Tomography imaging will play an important role in reducing costs, lowering administered radiation doses, and improving overall performance. PETALO employs liquid xenon as the active scintillating medium and UV-sensitive silicon photomultipliers for scintillation readout. The scintillation time in liquid xenon is fast enough to register time-of-flight information for each detected coincidence, and sufficient scintillation is produced with low enough fluctuations to obtain good energy resolution. The present simulation study examines a full-body-sized PETALO detector and evaluates its potential performance in PET image reconstruction.